Psychometric Properties of the Course Interest Survey (CIS) : A Confirmatory Factor Analysis - Hidayati, Nurkhairo; Mellisa, Mellisa; Armayati, Leni; Lestari, Rini Dwi; Oktaviani, Lala (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to evaluate the psychometric properties of the Indonesian version of the CIS using Confirmatory Factor Analysis (CFA). This research used an analytical approach and psychometric methods. Participants comprised 112 high school students aged 15 to 17 in Pekanbaru, Indonesia. CIS consists of 34 statement items with four subscales: attention, relevance, confidence, and satisfaction. Data analysis in Confirmatory Factor Analysis was carried out through MplusÂ 8.11 and SmartPLS. The results showed that CIS performed well on all psychometric indicators: CFI, TLI, RMSEA, outer loading, and AVE. The RMSEA value is 0.107 > 0.08, the CFI value is 0.710 < 0.90, the TLI value is 0.689 < 0.90, and the SRMR value is 0.098 > 0.08. All items and subscales in the motivation variable are valid with outer loading item values > 0.7 and AVE values > 0.5. Based on CFI and TLI, the CIS model is a good fit and can be accepted. Furthermore, the four dimensions or subscales of the CISâ€”namely, attention, relevance, confidence, and satisfactionâ€”demonstrate adequate psychometric properties. Based on the findings of this study, it can be concluded that the Indonesian version of the CIS is a valid, reliable, and robust instrument for assessing motivation. The implication of this research is that educators can assess student motivation using the CIS instrument because it has been proven to be able to measure elements of motivation.